Novo, S. et al. Aliskiren: Just a New Drug for Few Selected Patients or an Innovative Molecule Predestinated to Replace Arbs and Ace-Inhibitors? Pharmaceuticals 2009, 2, 118-124 - Giuseppina Novo; Elena Raccuglia; Antonino Mignano; Salvatore Novo; Giovanni Fazio (MDPI AG, 2011)
In the published version "Paladini et al. reported that aliskiren 300 mg provided a sustained BP-lowering effect beyond the 24-h dosing interval, with a significantly smaller loss of BP-lowering effect in the 24-48 h period after dose than irbesartan 300 mg or ramipril 10 mg [25]". Paladini et al. should be Palatini et al., and the cited reference number should be [10], not [25].. In the sentence, "Early data suggest a role for aliskiren in preventing end-organ damage but, considering the ONTARGET results with an ACE-I-ARB combination, outcome studies are needed before the use of aliskiren can be recommended in combination with other RAS inhibitors [18-30]" one more citation number was added [5], so the revised sentence is "Early data suggest a role for aliskiren in preventing end-organ damage but, considering the ONTARGET results with an ACE-I-ARB combination, outcome studies are needed before the use of aliskiren can be recommended in combination with other RAS inhibitors [5,18-30]". [...]